2005
DOI: 10.1016/j.nuclphysa.2005.02.077
|View full text |Cite
|
Sign up to set email alerts
|

Final-state interaction and recoil polarization in reactions: comparison with the polarized target case

Abstract: A study of the total cross section for polarized proton knockout in (e, e ′ p) reactions is carried out for the closed-shell nucleus 40 Ca. The dependence of FSI effects on polarization observables viewed as functions of the nucleon polarization angles is analyzed and interpreted within the basis of a semi-classical model for the orbit of the struck nucleon and trajectory of the ejected nucleon. A comparison with the case of a 39 K polarized target and unpolarized protons is performed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Moreover, the resulting semirelativistic (SR) current is simple enough to be easily implemented in already existing nonrelativistic models of (ν l , l − ) and (ν l , l + ) reactions, where l = e or µ. It is presented here as an extension of the electromagnetic and weak-neutral current expansion originally derived in [26] and that in recent years has been widely tested and applied in several Collaborations to describe a wide variety of inclusive and exclusive electron scattering observables for intermediate energies and excitations in the vicinity of the QE peak [27][28][29][30][31][32][33][34][35][36][37]. Extensions of the SR expansion to meson-exchange currents have also been developed [38,39], and a detailed description of their application to two-body currents can be found in a recent review article [40].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the resulting semirelativistic (SR) current is simple enough to be easily implemented in already existing nonrelativistic models of (ν l , l − ) and (ν l , l + ) reactions, where l = e or µ. It is presented here as an extension of the electromagnetic and weak-neutral current expansion originally derived in [26] and that in recent years has been widely tested and applied in several Collaborations to describe a wide variety of inclusive and exclusive electron scattering observables for intermediate energies and excitations in the vicinity of the QE peak [27][28][29][30][31][32][33][34][35][36][37]. Extensions of the SR expansion to meson-exchange currents have also been developed [38,39], and a detailed description of their application to two-body currents can be found in a recent review article [40].…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that in the independent particle model, this is a unit vector, |v| = 1, and that, semi-classically, it coincides with the local spin field in momentum space [31,32,39] (see an example in Appendix C for the particular case of the 39 K nucleus analyzed in the next section). Since the dependence of the cross-section on the final spin direction, S l N , is linear, one can write the ith component (i = x, y, z) of the vector cross-section in the general form…”
Section: Skewing Responses and Asymmetriesmentioning
confidence: 98%
“…500 MeV/c) the polarization induced by FSI is expected to be small (60.2). This is indicated both by experimental data [11] and by calculations [19,39]. the axes (z, x, y) used to characterize the bound nucleon (target) polarization.…”
Section: Single-nucleon Responsesmentioning
confidence: 99%
See 2 more Smart Citations